Fifty five years old male with gastrointestinal stromal tumor: a case report - Laura, Sylvia Frisca; Warsinggih, Warsinggih; Kusuma, M. Ihwan; Faruk, Muhammad (International Journal of Research in Medical Sciences, 2019)
Esophageal Gastrointestinal Stromal Tumors (GISTs) were extremely rare, with an incidence of 0,2% of GIST cases. Majority of esophageal GISTs were classified as high-risk category (70.83%), thus, it was required more aggressive approaches, e.g. radical surgery, chemotherapy and radiotherapy. This was a case of a 55-year-old male patient who was referred to surgery department complained of atypical chest pain and swallowing difficulty. Based on thorax X-Ray, it was suspected mediastinal mass. In addition, based on chest CT scan, it was suspected a mass at distal esophagus with multiple nodular lesions in liver dd/fatty liver. X-ray Oesophagus Maag Duodenum (OMD): Esophageal mass at 1/3 middle-distal part. Upper endoscopy diagnosis showed a fragile circularly spreading tumor mass which it was easily bleeds. Biopsy also showed a mild esophageal dysplasia with non-specific inflammation and necrotic tissue which was difficult to assess. This patient underwent McKeown esophagectomy. Moreover, pathology report showed diagnosis of a malignant tumor which fitted with criteria of malignant GIST, with both ends tumor-free. Finally, the patient was administered for imatinib as adjuvant therapy 1x400mg daily. This report illustrated complexity in diagnosing and treating esophageal GIST. The tumor size and mitotic rate of tumor were associated with poor survival.